Humic substances applications impact quality and yield of commercially-produced pomegranate saplings in Nangarhar, Afghanistan - Sándor, Ferenc; Tolner, László; Füleky, György; Abdiani, Saidajan A.; Sanchez, Jose E. (COLUMELLA – Journal of Agricultural and Environmental Sciences, 2015)
The efficacy and reliability of humic substances for increasing crop yields have not been widely established in the scientific literature. The aim of this research was to measure the effect of humic and fulvic acid application on the number of harvested pomegranate saplings, which meet the required standards and to compare it with saplings produced without humic substances. The application of humic substances increased by 34% the number of harvested pomegranate saplings meeting the requirements of the established standard. It improved quality characteristics of the saplings as well, such as increased weight and volume of the root system and increased diameter and height of the plant.
Keywords: humic acid; nutrient uptake; yield components; saplings quality standards